The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/jb.00927-15
|View full text |Cite
|
Sign up to set email alerts
|

Formate Metabolism in Shewanella oneidensis Generates Proton Motive Force and Prevents Growth without an Electron Acceptor

Abstract: Shewanella oneidensis strain MR-1 is a facultative anaerobe that thrives in redox-stratified environments due to its ability to utilize a wide array of terminal electron acceptors. Conversely, the electron donors utilized by S. oneidensis are more limited and include products of primary fermentation such as lactate, pyruvate, formate, and hydrogen. Lactate, pyruvate, and hydrogen metabolisms in S. oneidensis have been described previously, but little is known about the role of formate oxidation in the ecophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 36 publications
0
48
0
Order By: Relevance
“…4). Using GlcNac and lactate as sole carbon sources and fumarate as the sole electron acceptor, the biomass production and reaction flux distributions of the WP3 wild-type and mutant models revealed that substrate-level phosphorylation was the primary source of anaerobic energy conservation, a trait that has been noted in MR-1 (8, 10). This indicates that the primary usage of substrate-level phosphorylation could be a conserved feature in the anaerobic respiration of both group 1 and group 2 species and suggests that this feature could have evolved during the early differentiation of Shewanella .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…4). Using GlcNac and lactate as sole carbon sources and fumarate as the sole electron acceptor, the biomass production and reaction flux distributions of the WP3 wild-type and mutant models revealed that substrate-level phosphorylation was the primary source of anaerobic energy conservation, a trait that has been noted in MR-1 (8, 10). This indicates that the primary usage of substrate-level phosphorylation could be a conserved feature in the anaerobic respiration of both group 1 and group 2 species and suggests that this feature could have evolved during the early differentiation of Shewanella .…”
Section: Discussionmentioning
confidence: 92%
“…Several recent studies have focused on identifying the relative contributions of two distinct ATP-producing mechanisms (810), oxidative phosphorylation and substrate-level phosphorylation. Oxidative phosphorylation is typically associated with respiration, where the reduction of terminal electron acceptors is coupled to proton motive force (PMF) generation, and the PMF subsequently contributes to ATP synthesis via ATP synthase (ATPase).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to S. oneidensis , Ca . Brocadia electricigens gets a significant amount of proton motive force and feeds the quinol pool in the inner membrane by transporting and oxidizing formate in the periplasm ( 85 ) (Fig. S10).…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…1A, indicating the reduction of metal ions into (a) Pd and (b) Au NPs by the bacteria. 14,15 As measured at 600 nm, the light-scattering intensity of a single cell increased strongly after incubation in the suspensions, including the palladium ion, and became constant after 1 h (Fig. 1B).…”
Section: -14mentioning
confidence: 99%